Is There A Fe(Male) Approach In Customer Relationship Management? - Tedy Herlambang (Universitas Airlangga, 2009)
Customer relationship management (CRM) has been the favorite topic of scores of marketing consultants and academicians for over a decade. CRM approaches marketing as dating in which the marketer attempts to turn strangers into friends and friends into lifetime partners and to retain the loyalty of the right customers for this is the key to long-term profits in a company. Gender theories posit that women and men behave differently, and that they approach things differently. Moreover, these theories have documented a picture of women are being more expert and motivated relationship psychologists than men, as more active in their relationship monitoring, and as more oriented toward the maintenance and success of their relationships. Based on these theories, this paper develops some propositions to facilitate its empirical testing related to relationship communication and relationship dissolution in business market. The contribution of this paper is twofold. First, it attempts to create more insight into areas where relationship marketing research to date has not been abundant. Second, this paper attempts to contribute to methodological development of measuring relationship success by systematically distinguishing between good communication relationship and good management relationship.